POLITENESS STRATEGIES USED BY THE MAIN CHARACTERS IN FINDING OHANA (2021) MOVIE - Nurmaida Panjaitan; Elisa Betty Manullang (State University of Medan, 2022)
This study was conducted by using descriptive qualitative method. It was concerned with the description of the data in the form of utterances prodused by the main characters in Finding Ohana (2021) Movie. In conducting this research, the researcher (1) found out the types of politeness strategy in Finding Ohana (2021) Movie. (2) described the realization types of politeness strategies in Finding Ohana (2021) Movie. (3) explain the reason why the types of politeness strategies using in Finding Ohana (2021) Movie. The data of this research was the utterances by the main characters in the movie, that was English subtitle. In the application of the politeness strategies, the Finding Ohana (2021) Movie utterances mostly applied Bald on Record strategy. The result showed that most dominant type of politeness strategies is Bald on Record strategy (43,3%). Consequtively the percentage of Positive Politeness strategy was (36.1%). The percentage of Negative Politeness was (14,4%). The lowest percentage of politeness strategy is Off Record with (6.2%). The reason why the types of politeness strategies using in the Finding Ohana (2021) movie, instead of each politeness strategies has sub-strategies which explained those utterances contained politeness strategies and also influenced by payoffs and sociological variables